2004
DOI: 10.1016/j.virol.2004.06.002
|View full text |Cite
|
Sign up to set email alerts
|

H5N1 chicken influenza viruses display a high binding affinity for Neu5Acα2-3Galβ1-4(6-HSO3)GlcNAc-containing receptors

Abstract: To characterize differences in the receptor-binding specificity of H5N1 chicken viruses and viruses of aquatic birds, we used a panel of synthetic polyacrylamide (PAA)-based sialylglycopolymers that carried identical terminal Neu5Acalpha2-3Gal fragments but varied by the structure of the next saccharide residues. A majority of duck viruses irrespective of their HA subtype, bound with the highest affinity to trisaccharide Neu5Acalpha2-3Galbeta1-3GlcNAc, suggesting that these viruses preferentially recognize sia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
63
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(70 citation statements)
references
References 32 publications
6
63
1
Order By: Relevance
“…Consistent with our findings, these studies have shown that an H3N2 virus binds to the ciliated cells of the human trachea (52). Complex variations in carbohydrate structures may also contribute to binding of viruses and account for differences in infection of human and avian strains; however, this work is still evolving (14).…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with our findings, these studies have shown that an H3N2 virus binds to the ciliated cells of the human trachea (52). Complex variations in carbohydrate structures may also contribute to binding of viruses and account for differences in infection of human and avian strains; however, this work is still evolving (14).…”
Section: Discussionsupporting
confidence: 89%
“…The strong preference observed for α2,3-linked over α2,6-linked sialosides is in agreement with previously reported results for equine viruses (17). Similarly, the greater avidities of equine viruses for analogs containing sulfated GlcNAc3 residues have been reported before (18)(19)(20). Ef virus binds 3′ sialylactosamine (3′SLN) with about 1/3rd the avidity of Ee and the other three analogs, Sialyl Lewis X (SLe x ), sulfated Sialyl Lewis X (Su-SLe x ), and Su-3′SLN, with about 1/10th the avidity of Ee (Fig.…”
Section: Significancesupporting
confidence: 93%
“…There is evidence that some chicken and mammalian influenza A viruses display a high binding affinity for sulfated sialylglycan receptor, and this binding affinity is decreased after treatment of cells with sulfatase [50]. The presence of sulfated Neu5Ac(α2→6)Gal in CAM and AM cells (1.3% and 3.8%, respectively, Table 1) may facilitate human influenza virus infection of AM cells.…”
Section: Methodsmentioning
confidence: 99%